1997
DOI: 10.1302/0301-620x.79b3.0790433
|View full text |Cite
|
Sign up to set email alerts
|

External Fixation and Secondary Intramedullary Nailing of Open Tibial Fractures

Abstract: We performed a prospective, randomised trial in 39 patients with open tibial fractures treated initially by external fixation to compare cast immobilisation (group A) and intramedullary nailing (group B) as a sequential protocol planned from the onset of treatment.The results showed that group B achieved faster union (p < 0.05) than group A with less malunion or shortening and a greater range of movement. Patients treated by intramedullary nailing required fewer radiographs and outpatient visits (p = 0.0015) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Nevertheless, good results have been reported in grade I and II open fractures [5, 9,15], and there are reports of a good outcome with its use in grade III cases [7,15]. Some authors have used delayed intramedullary nailing after initial external fixation in order to avoid the disadvantages, and report good results [1,2]. Flexible nails [11,12] or small diameter rigid nails [13,29] have been tried with the aim of avoiding disturbance of cortical vascularity and increase of compartmental pressure, but with a significant number of cases of malunion.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, good results have been reported in grade I and II open fractures [5, 9,15], and there are reports of a good outcome with its use in grade III cases [7,15]. Some authors have used delayed intramedullary nailing after initial external fixation in order to avoid the disadvantages, and report good results [1,2]. Flexible nails [11,12] or small diameter rigid nails [13,29] have been tried with the aim of avoiding disturbance of cortical vascularity and increase of compartmental pressure, but with a significant number of cases of malunion.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that secondary IM nailing is associated with a better outcome, when compared to secondary treatment in plaster [2].…”
Section: Introductionmentioning
confidence: 99%
“…Clasper et al 11 reported that presence of pin track infection at the same place and time of IMN can predispose to infecting the internal fixation device However, internal fixation after removal of EF is known to have low risk of infection and good union rate. 10,15,17,23 Wu and Chen 10 presented a technique for speedy pure lengthening, not segment transfer and no docking site problems, of short tibia because of aseptic nonunion, poliomyelitis, and/or malunion by EF with rate of 1 to 1.5 mm per day followed by internal fixation using plates or static IMN, once the lengthening achieved, without waiting for new bone to consolidate. Bone graft was used during the procedure of internal fixation to accelerate distracting callus maturation.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] In contrary, other authors described the use of intramedullary nailing after removal of EF, as in an open fracture tibia, with good results regarding bone healing without residual infection. [15][16][17][18] This study used the Ilizarov technique and EF system to remove dead bone, eradicate infection, and reconstruct the limb using a segment transport, to replace the removed bone by new bone from the corticotomy site. After finishing the segment transport, the EF was removed and replaced by intramedullary nailing, aiming to allow more patient comfort, fewer complications, and earlier rehabilitation than from EF alone.…”
mentioning
confidence: 99%